2020
DOI: 10.1039/d0lc00001a
|View full text |Cite
|
Sign up to set email alerts
|

In situ generation of plasma-activated aerosols via surface acoustic wave nebulization for portable spray-based surface bacterial inactivation

Abstract: We demonstrate an efficient technique for in situ production and application of plasma-activated aerosols for surface disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 120 publications
1
28
0
Order By: Relevance
“…1 (a–iii) and 1 (b–i) that the entire paper strip, with a width of 8 mm and a length greater than 10 mm, is exposed to the plasma that is generated by the thousands of nanorods, each of which resembles a nanoscale needle. This is, in contrast, to the cometary discharge setup using a single (or two) point sources in preceding work 15 , where exposure across a small spot of approximately ϕ pls ≈ 3 mm on the paper strip could only be achieved albeit at higher intensities.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…1 (a–iii) and 1 (b–i) that the entire paper strip, with a width of 8 mm and a length greater than 10 mm, is exposed to the plasma that is generated by the thousands of nanorods, each of which resembles a nanoscale needle. This is, in contrast, to the cometary discharge setup using a single (or two) point sources in preceding work 15 , where exposure across a small spot of approximately ϕ pls ≈ 3 mm on the paper strip could only be achieved albeit at higher intensities.…”
Section: Resultsmentioning
confidence: 75%
“…As such, a rapid and miniaturized system that facilitates on-demand generation of plasma-activated water at the point-of-use for surface decontamination constitutes a significant practical advantage over conventional systems. While our previous study conceptually demonstrated the possibility of generating aerosols with a portable nebulization system that was subsequently plasma-activated using cometary discharge for spray-deposition of surfaces for bacterial inactivation 15 , the use of two cometary discharge systems to provide sufficient uniform areal plasma coverage to activate the water feed to the nebulizer to be aerosolized, however, prevented integration into a compact and lightweight miniaturized setup that facilitates portable operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, all three types of solutions showed significant effects. As another example of vaporized application, Wong et al treated deionized water with plasma and then made an aerosol with acoustic waves to see the antimicrobial activity, which showed a 95% reduction in 30 min of treatment [66]. These experiments show that PAL has an antimicrobial effect not only in the bulk liquid state, but also in vaporized or aerosol form.…”
Section: Sterilization and Disinfectionmentioning
confidence: 99%
“…For a more detailed description of plasma sources, see papers [ 1 , 2 , 3 ]. A special DC discharge called cometary was described by Scholtz and Julák [ 4 , 5 ] and used, among others, by Wong et al [ 6 ]. The point-to-ring arrangement of the corona discharge has been applied in onychomycosis therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%